1990
DOI: 10.1126/science.1972596
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Allogeneic Cells on the Human T and B Cell Repertoire

Abstract: Clinical transplantation is often complicated by rejection episodes, in which the immune system of the recipient reacts to the foreign transplantation (HLA) antigens on the graft. This immune response includes humoral and cellular components. In the first, B lymphocytes form antibodies to the HLA alloantigens. In the second, CD8+ T lymphocytes recognize and react to HLA class I antigens, and CD4+ T cells react to HLA class II antigens. The frequency and severity of these rejection episodes can be diminished by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(34 citation statements)
references
References 48 publications
2
30
2
Order By: Relevance
“…31 This observation was apparently in keeping with data published by some authors on a blunted immune response to maternal cells or soluble HLA antigens, 30,33,34 but in contrast with results reported by others, 32,35 who did not show any difference in the CTLp frequency towards NIMA and NIPA. Results of the present study indicate that absence of response in 'bulk culture' does not seem to be due to deletion of NIMA-reactive cytotoxic cells, but it can rather be attributed to the action of regulatory populations, displaying their effect in 'bulk culture' and unable to carry out their function in a limiting dilution condition.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…31 This observation was apparently in keeping with data published by some authors on a blunted immune response to maternal cells or soluble HLA antigens, 30,33,34 but in contrast with results reported by others, 32,35 who did not show any difference in the CTLp frequency towards NIMA and NIPA. Results of the present study indicate that absence of response in 'bulk culture' does not seem to be due to deletion of NIMA-reactive cytotoxic cells, but it can rather be attributed to the action of regulatory populations, displaying their effect in 'bulk culture' and unable to carry out their function in a limiting dilution condition.…”
Section: Discussioncontrasting
confidence: 52%
“…29 However, these favourable clinical effects of NIMA have not found a biological explanation, since conflicting results on development of NIMA-specific CTL have been published. [30][31][32][33][34][35] We previously observed that CBMC from about 50% of neonates are unable to develop CTL activity when challenged in vitro with allogeneic cells in 'bulk culture' conditions. In the great majority of remaining individuals who were able to mount a cytotoxic response against paternal cells, CBMC were unable to kill cells of maternal origin.…”
mentioning
confidence: 99%
“…Donor-specific transfusions (DST) 3 induce both experimental and clinical donor-specific allograft tolerance (15,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Development Of Infectious Tolerance After Donor-specificmentioning
confidence: 99%
“…Finally, in contrast to other experiences we were able to achieve excellent cell recovery using a Ficoll though to be due to the development of tolerance in utero to the non-inherited maternal allele. 24,25 In this case the gender separation technique resulting in prompt engraftment after infusion of cryopreserved cells. We therefore conclude that equity of the patient and donor and the low parity of the mother also decreased the likelihood of GVHD occurring.…”
Section: Parameter Resultsmentioning
confidence: 99%